Determinants of Fertility, Women's Health and Employment Behavior in Sri Lanka - World Bank (Washington, DC, 2014)
The paper analyzes the labor market during 1992-2009, the wartime years, and uses the findings to help understand implications for the labor market as the economy grows and recovers from the conflict. The analysis is primarily based on annual Labor Force Survey (LFS) data collected by the Department of Census and Statistics (DCS) between 1992 and 2009. The paper excludes the North and East from the analysis because the labor market in these provinces was functioning in atypical times, and was affected severely by the security situation. The 2006 moving out of poverty study conducted in conflict areas noted large outmigration of the better off households and the reliance on those left behind on remittances (Center for Poverty Analysis 2006). The study also found that private sector investment had largely dwindled in these provinces, and the main source of jobs was public employment. Looking ahead, over the next 15 years, demand for workers in industry is likely to increase as rebuilding and recovery in the North and East proceeds. In addition, demand for highly skilled workers to meet the needs of the expanding services sector, particularly higher-end services, will also increase. Analyzing the empirical trends using the LFS, it is clear that increasing female labor force participation, addressing high youth unemployment and its causes, and addressing the negative aspects of certain labor market regulations will be key to meeting the needs of a growing economy. The paper is organized as follows. The two sections that follow present an overview of the supply and demand side of the labor market. The next section discusses the ways in which the demographic transition could shape the labor market, particularly in terms of unemployment and earnings. This discussion is followed by three sections examining labor force participation and unemployment, job type, and earnings respectively. The last section concludes with some policy recommendations.